Pengaruh Collateral Asset, Sales Growth dan Free Cash Flow Terhadap Dividend Policy - Juniarti, Windi; Utami, Tri (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study aims to test and analyze the effect of collateral assets, sales growth, and free cash flow on dividend policy. This study uses a sample of property and real estate sector companies listed on the Indonesia Stock Exchange in 2019-2023 with a population of 92 companies. The sampling technique in this study was the purposive sampling method, so that 7 companies were selected, with 5 years of observation, so the number of observations in this study was 35 data. The research method used was an associative method with a quantitative approach. The data analysis technique used Microsoft Excel and E-views version 9 tools by conducting descriptive statistical tests, panel data regression model tests, classical assumption tests, and hypothesis tests. Simultaneously shows that collateral assets, sales growth, and free cash flow have an effect on dividend policy. Partially, collateral assets have no effect on dividend policy. Meanwhile, sales growth has a positive effect on dividend policy and free cash flow has a negative effect on dividend policy